INVESTMENT SIMULATION OF REPLACING PRODUCTION MACHINERY AT A RICE FACTORY SUKORENO MAKMUR - Rizky Dwi Prawoto, Isti Fadah & Sumani (International Journal of Research Science and Management, 2019)
This study aims to assess the feasibility of investing in production machinery replacement in the Sukoreno Makmur rice mill business. In this study, Monte Carlo simulation was used to project various conditions that might occur in the future. This study uses 3 methods to assess the feasibility of investing in production machinery replacement, namely NPV, IRR, and DPP methods. The results of the calculation show that the investment plan for replacing the old production machine with a new production machine is feasible with the result of a positive NPV value, the IRR value is greater than the WACC value, and the payback time is equal to the expected payback time of the company owner. In this study data data to be simulated are production costs, sales revenue, and bank loan interest rates.